Anti-aging treatments slow propagation of synucleinopathy by restoring lysosomal function. Issue 10 (2nd October 2016) - Kim, Dong-Kyu; Lim, Hee-Sun; Kawasaki, Ichiro; Shim, Yhong-Hee; Vaikath, Nishant N.; El-Agnaf, Omar M. A.; Lee, He-Jin; Lee, Seung-Jae
ABSTRACT: Aging is the major risk factor for neurodegenerative diseases that are also associated with impaired proteostasis, resulting in abnormal accumulation of protein aggregates. However, the role of aging in development and progression of disease remains elusive. Here, we used Caenorhabditis elegans models to show that aging-promoting genetic variations accelerated the rate of cell-to-cell transmission of SNCA/α-synuclein aggregates, hallmarks of Parkinson disease, and the progression of disease phenotypes, such as nerve degeneration, behavioral deficits, and reduced life span. Genetic and pharmacological anti-aging manipulations slowed the spread of aggregates and the associated phenotypes. Lysosomal degradation was significantly impaired in aging models, while anti-aging treatments reduced the impairment. Transgenic expression of hlh-30p::hlh-30, the master controller of lysosomal biogenesis, alleviated intercellular transmission of aggregates in the aging model. Our results demonstrate that the rate of aging closely correlates with the rate of aggregate propagation and that general anti-aging treatments can slow aggregate propagation and associated disease progression by restoring lysosomal function.